Predisposing Factors to Medication Errors by Nurses and Prevention Strategies: A Scoping Review of Recent Literature - Fábio Coelho; Luís Furtado; Natália Mendonça; Hélia Soares; Hugo Duarte; Cristina Costeira; Cátia Santos; Joana Pereira Sousa (MDPI AG, 2024)
Medication errors have serious consequences and high costs for the patient and the system. The treatment process and the care required for critically ill patients are complex, and these patients are more vulnerable to errors and potential consequences. A scoping review using the JBI methodology was conducted across PubMed, CINAHL, and MEDLINE databases and reported by the PRISMA-ScR guidelines to explore strategies that can mitigate medication errors by nurses. The search strategy focused on references published between January 2012 and April 2023. Sixteen studies were included, and the results were organized into thematic areas. Medication errors by nurses are in the areas of preparation, administration, and documentation; organizational, system-related, procedural, personal, and knowledge and training factors are predisposing factors for errors; educational intervention, verification and safety methods, organizational changes, and error reporting are the strategic areas to mitigate medication error. The organization of the data could be different, as it depends on the reviewers' experience. Knowledge of the factors that cause medication errors and interventions to mitigate them make it possible to outline strategies to minimize their occurrence and achieve health gains. The protocol preceding this review has been registered in the Open Science Framework and published.